WITNESS PROTECTION MECHANISM UNDER INDIAN LEGAL FRAMEWORK: AN ANALYSIS - Ankit; Dhull, Jitender Singh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Compared to other jurisdictions, a comprehensive analysis of the mechanisms for the protection of witnesses in India is provided. The research paper addresses the worrying vulnerability of witnesses in the Indian Criminal Justice System, where threats, intimidation and harassment are frequent, resulting in weakened trials and unjust results. Despite some recent developments, India's legal framework does not yet have the institutionalized infrastructure necessary to protect effective witnesses. The study compared India with the US, which has an extensive witness security program, the UK and other countries with a wide range of long-standing protection plans and highlighted the importance of structured government programs to ensure the safety of witnesses. The analysis looks at the different approaches adopted by these countries, pointing out that jurisdictions such as the US provide multiple security options such as relocation, financial support and new identity. At the same time, India is still largely dependent on measures. The comparisons reveal essential gaps in the framework, particularly the need for dedicated agencies and resources to systematically protect witnesses. The study advocates urgent reforms of the Indian legal system, drawing on best international practice. Establishing a robust witness protection program will not only improve the fairness of trials. Still, it will also encourage more witnesses to be present without fear, thereby strengthening the rule of law and the provision of justice.